'Deal or No Deal?': Assessing the UK's New Green Deal. Issue 2 (1st June 2014) - Reid, Louise
Abstract : The UK government has recently implemented the Green Deal, a new pay-as-you-save policy which seeks to fundamentally reform the existing housing stock to make it more energy efficient. Regarded by its proponents as a 'revolutionary programme to bring our buildings up to date' (HM Government 2010: 2), generate cash savings for householders, and simultaneously yield environmental benefits by reducing energy consumption, it promises much. However, there have been many critiques of the Green Deal from industry, environmental pressure groups and housing professionals. Moreover there has been very limited take up of Green Deal loans by householders, and those measures which have been installed offer perhaps only minimal improvements in overall energy efficiency. This paper therefore considers the potential generative and productive outcomes of the Green Deal by looking across three related issues: households with low incomes and in fuel poverty; the potential impacts on elements of the housing system; and, the extent of environmental benefits. The paper concludes by suggesting that the instead of being a revolutionary way to improve the energy efficiency of the UK's domestic building stock, the Green Deal may potentially perpetuate existing social injustice and environmental degradation. The effort should, instead, focus on understanding how energy demand is created in the first place (e.g. desire for larger homes, energy-hungry appliances, heating in every room) through householders' expectations and changing domestic practices.